Antimicrobial activity of ocimum gratissimum extract on suya (an intermediate moisture meat) in Nigeria (2014)
Matured leaves of Ocimum gratissimum were harvested and the extracts used to cure Suya (an intermediate moisture meat). O. gratissimum leaves were collected from Oyo state south west region of Nigeria, rinsed in distilled water and squeezed to extract the fluid. The meat used was Semi membranosus muscle from beef carcass, which was trimmed of all visible fat and connective tissues. The meat cut was sliced into sheets of 0.18cm-0.35cm thick and lengths of between 5.0cm-7.1cm. The study comprised five treatments with 10 replicates each in a completely randomized design. Treatment A (TA) served as the control (Suya without O. gratissimum extract(OGE), while treatment B (TB),treatment C (TC), treatment D (TD) and treatment E (TE) were Suya soaked in OGE for ½ hr, 1hr, l½ hrs and 2 hrs, respectively, before coating with Suya ingredients. A total of 50 sticks of Suya weighing from 38.10 - 59.30 grams of sliced meat per stick were prepared for each treatment. The meat on sticks was properly coated with Suya ingredients and arranged around glowing embers of charcoal. The morphological and biochemical characterization of aerobic bacteria, coliform and lactic acid isolates from the five treatments was carried out. At Day 0, isolates from samples of the five treatments include: Aerobic species of Pseudomonas, Bacillus, Micrococcus, and Flavobacterium species. Three Coliform species isolated were: Proteus, Aeromonas and Enterobacter species. The four Lactic acid bacteria isolated were Pediococcus, Streptococcus, Lactobacillus species and Enterococcus feacalis. The bacterial count on Suya meat soaked in OGE at different curing times of ½ hr, 1hr, 1½ hrs and 2hrs differed. The aerobic counts (0.001x105- 2.2x105) were relatively low at the third and fifth days for TC, TD, and TE while for Lactic acid bacteria, the count reduced from 3.0x105 in TA to 0.2x105 in TE. Coliform counts of 6.0x105 and 7.0x105 recorded at day 7 for TA and TB were exceptionally high. O. gratissimum extract, used as a curing agent in suya production significantly reduced the aerobic count of treated meat, thus enhancing the keeping quality of the products.